Spatial orientation in four-year-olds from a public and private school - Neyra Fernández, Leidy Melissa (2019)
The objective of this research was to determine the difference in spatial orientation in four-year-old children of a Public Educational Institution and a Private Educational Institution, Lima. The theoretical foundations were based on the theory of Jean Piaget, which refers to the cognitive processes developed according to the age of the infants, which are related to the stages of space acquisition. In addition, Howard Gardner's theory of spatial intelligence was considered. The research is basic type, comparative descriptive level. A checklist was used as an instrument. 0.023 (p <.005) was obtained, that is, there is a difference in spatial orientation in four years in favor of the private educational institution.